1998
DOI: 10.1021/jf980310p
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Selected Medicinal Plants

Abstract: Commonly used medicinal plant extracts with standardized content of polyphenols were investigated for their total antioxidant activity (TAA). Green tea, oligomeric procyanidins (from grape seed and pine bark), bilberry, and ginkgo exhibited TAA in the range of 5.12−2.57 mM Trolox, thereby indicating a valuable antioxidant capacity. Witch hazel, propolis EPID, artichoke, and hawthorn afforded lower TAA (1.54−0.44 mM Trolox), whereas echinacea, ginseng, passionflower, sweet clover, and eleuthero were rather unef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
146
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(159 citation statements)
references
References 21 publications
(17 reference statements)
9
146
1
3
Order By: Relevance
“…Aoshima et al (14) as well as Pie a et al (17) reported close correlations between the phenolic content and antioxidant capacity of ginkgo leaf extracts. In case of collected ginkgo leaves, Sati et al (18) found a strong positive correlation between the phenolic content and antioxidant capacity measured by the FRAP assay However, Ronowicz et al (19) documented a signifi cant negative correlation (R = -0.7668, p ≤ 0.01) between the total phenolic content and antioxidant activity (measured by DPPH method) for commercial ginkgo preparations.…”
Section: Correlation Between Total Phenolic Content and Antioxidant Cmentioning
confidence: 84%
“…Aoshima et al (14) as well as Pie a et al (17) reported close correlations between the phenolic content and antioxidant capacity of ginkgo leaf extracts. In case of collected ginkgo leaves, Sati et al (18) found a strong positive correlation between the phenolic content and antioxidant capacity measured by the FRAP assay However, Ronowicz et al (19) documented a signifi cant negative correlation (R = -0.7668, p ≤ 0.01) between the total phenolic content and antioxidant activity (measured by DPPH method) for commercial ginkgo preparations.…”
Section: Correlation Between Total Phenolic Content and Antioxidant Cmentioning
confidence: 84%
“…They are hazardous in high amount and interfere with proteins, enzymes, RNA and DNA, leading to tissue injury and degenerative diseases [12,13] . Mammalian body has certain protection mechanisms to combat and reduce oxidative injury.…”
Section: In Vitro Antioxidant and Cytotoxic Effects Of Methanol Extramentioning
confidence: 99%
“…If not eliminated, ROS can attack important biological molecules, such as lipids, proteins, enzymes, DNA and RNA (Jung, Park, Chung, Kim, & Choi, 1999;Pietta, Simonetti, & Mauri, 1998;Yen & Chen, 1995). Although the human body possesses many defence mechanisms against oxidative stress, including antioxidant enzymes and non-enzymatic compounds, an excess of free radicals can go out of control, the organism being unable to scavenge all ROS (Halliwell, Aeschbach, Löliger, & Aruoma, 1995;Miyake et al, 2000;Sies, 1993;Tseng et al, 1997).…”
Section: Introductionmentioning
confidence: 99%